Enhancing RSA algorithm using Mersenne Primes with reduced size of encrypted file (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Message passing from source to destination is one of the important aspects of communication. However, it is requiredmany times that this message gets transmitted secretly, so that no unauthorized person gets knowledge of the contents ofthat message. To retain the confidentiality of the message transmitted is a challenging task as it needs to be guaranteedthat the message arrive in the right hands exactly as it was transmitted. Another challenge is of transmitting the messageover a public, insecure channel. In this paper, RSA algorithm is implemented using Mersenne Primes which guaranteesthe primality. This is an enhanced algorithm which increases the strength of RSA by generating large prime numbers andalso reduces the size of encrypted file.